1997
DOI: 10.1097/00001888-199708000-00021
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two methods to teach smoking-cessation techniques to medical students

Abstract: Although the students rated the SPs higher than they did the role playing, the two tools produced similar levels of skills attainment. The data suggest that having students practice smoking-cessation techniques through role playing may be as effective as using the more extensive SPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 0 publications
3
62
0
Order By: Relevance
“…This review examined studies where communication skills were taught for a number of different contexts, including sexual health [25,34,36], breaking bad news [23], behavior change [30,31,38,[42][43][44], cancer [9,39] and domestic violence [24,33]. Trainees may, for whatever reason, have found it easier to implement communication skills in some contexts rather than others, and this warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review examined studies where communication skills were taught for a number of different contexts, including sexual health [25,34,36], breaking bad news [23], behavior change [30,31,38,[42][43][44], cancer [9,39] and domestic violence [24,33]. Trainees may, for whatever reason, have found it easier to implement communication skills in some contexts rather than others, and this warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Papadakis et al [44] compared the use of role-play with the use of simulated patients in teaching smoking cessation skills to first year medical students. All students received lectures and written information on the effects of smoking and how patients can be helped to stop.…”
Section: The Use Of Simulated Patients In Training Versus the Use Of mentioning
confidence: 99%
“…49 -51 Some comparative studies also reported views of students on the instruction they had. [52][53][54] All of these studies showed students preferred instruction by SP-teachers to teaching by physicians or to traditional teaching methods such as role-playing. Several studies primarily focused on student evaluations with regard to instruction by SP-teachers.…”
Section: Sps As Teachers: Sp-teachersmentioning
confidence: 99%
“…Less than half of all studies within the review specifically assessed student performance following the intervention (Campbell et al, 1996;Papadakis et al, 1997;Bosse et al, 2012;Saba et al, 2014). In addition, only four studies assessed student self-efficacy in relation to patient education (James et al, 2003;Goldenberg et al, 2005;Bosse et al, 2012).…”
Section: Patient Education Training For Health Professional Studentsmentioning
confidence: 99%
“…Most research to date includes components of patient education within the wider context of patient communication skills and refers to patient education skills in general terms, without defining educational content or specific competencies. Secondly, few studies have included direct assessment of some aspects of student performance in patient education following training (Lorenz, 1987;Campbell et al, 1996;Papadakis et al, 1997;Bosse et al, 2012).…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%